2003
DOI: 10.21273/jashs.128.6.0838
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Lychee (Litchi chinensis Sonn.) Cultivars and their Genetic Relationships Using Intersimple Sequence Repeat (ISSR) Markers

Abstract: There is widespread confusion and uncertainty concerning the identity of lychee cultivars: the same cultivar may be known under different names and different cultivars may appear under the same name. In the present study, the potential of intersimple sequence repeat (ISSR) for the identification of 66 lychee cultivars and accessions and a determination of their genetic relationships was evaluated, using 32 primers containing different simple sequence repeat motifs. Of the 194 bands produced, 124 (64%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
5
20
0
3
Order By: Relevance
“…Our PPB values fell within the range of variability reported in studies using dominant molecular markers to discriminate between taxa at the species level and below (Loo et al ., 1999; Degani et al ., 2003; Schrader & Graves, 2004; Tian et al ., 2004). For example, the number of total and polymorphic RAPD bands (97 and 65, respectively; PPB = 67%) reported in a study of Licuala glabra Griff.…”
Section: Discussionmentioning
confidence: 99%
“…Our PPB values fell within the range of variability reported in studies using dominant molecular markers to discriminate between taxa at the species level and below (Loo et al ., 1999; Degani et al ., 2003; Schrader & Graves, 2004; Tian et al ., 2004). For example, the number of total and polymorphic RAPD bands (97 and 65, respectively; PPB = 67%) reported in a study of Licuala glabra Griff.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the cultivars bear distinctly small to rudimentary seed and larger flesh. The morphological features are affected by climate and soil conditions, and this sometimes causes confusion in naming the cultivars (Degani et al, 2003;Huang et al, 2005). Seedlings of certain cultivars are morphologically similar and thus are often misidentified.…”
mentioning
confidence: 99%
“…The modification included the addition of Sorbitol buffer before CTAB buffer extraction to minimize the high mucus content of the leaves, and also the addition of repeated DNA purification process to separate polysaccharide and other secondary metabolite residues from the DNA samples. Six out of 31 ISSR primers (Degani et al 2003, Hariri 2017, Riupassa 2016 were selected to produce the clearest and showed the highest polymorphic INTRODUCTION Rambutan (Nephelium lappaceum L.) is one of tropical fruit that has a high potential value. It belongs to Sapindaceae which originated from South East Asia primarily in Indonesia and Malaysia (Leenhouts, 1986).…”
Section: Dna Isolation Amplification and Visualizationmentioning
confidence: 99%